ANALISIS PENGUATAN KARAKTER TANGGUNG JAWAB PADA SISWA SEKOLAH DASAR YANG MENGIKUTI BIMBINGAN BELAJAR DI LUAR SEKOLAH - Silmi Fadhila Arida; Wawan Shokib Rondli; Khamdun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The issue of students' dependence on tutoring teachers is increasingly becoming a bad habit. This makes the purpose of this research to analyze the strengthening of the character value of responsibility among fourth-grade students at SD 2 Singocandi, particularly those who attend tutoring outside of school. This research uses a qualitative research type with a narrative inquiry approach, which will then be explained descriptively. Using data collection techniques such as observation, interviews, and documentation, as well as using Miles and Huberman's data analysis techniques, namely data reduction, data presentation, and conclusion. The results obtained through this research indicate that the responsibility character of the 4th-grade students at SD 2 Singocandi, particularly those who attend extracurricular tutoring, falls into the good category. The efforts made by teachers at school or educators in tutoring sessions have proven to provide good progress in the students' sense of responsibility. Moreover, influenced by several factors both from within the students themselves and from their environment, the stages in strengthening the value of students' responsibility character become even better.